Comparison of Mechanical and Low-Frequency Dielectric Properties of Thermally and Thermo-Mechanically Aged Low Voltage CSPE/XLPE Nuclear Power Plant Cables - Ramy S. A. Afia (MDPI AG, 2021)
During the service period of low-voltage nuclear cables, multiple stresses influence the aging of polymeric materials of cables. Thermal and radiation stresses are considered service aging factors in qualification tests, while the standards usually do not prescribe mechanical stress. CSPE/XLPE insulated nuclear cable samples were exposed to thermal and combined thermo-mechanical aging for more than 1200 h at 120 °C. The real and imaginary parts of permittivity were measured in the 200 μHz to 50 mHz range as dielectric properties. The Shore D hardness of the samples was measured to analyze the mechanical characteristics of the cable. To characterize the dielectric spectrum, derived quantities, namely central real and imaginary permittivities and real and imaginary permittivities’ central frequencies were calculated. The change of dielectric spectra did not show a clear trend with aging, but the imaginary permittivity’s central frequency was higher by 0.5 mHz in the case of thermo-mechanically aged samples. The Shore D hardness was also higher on the thermo-mechanically aged samples. These findings show the combined aging has a higher impact on the insulation properties. Hence, involving the mechanical stress in the aging procedure of cable qualification enables the design of more robust cables in a harsh environment.